When evocative things travel : the roles of material objects in the process of Muslim migrants' settlement : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology, Massey University, Albany, New Zealand - Sultana, Shahnaj (Massey University, 2022)
This thesis examines materiality, migration and settlement through the roles objects play in supporting Muslim migrants, to negotiate the uncertainties associated with settlement in an unfamiliar location. It focusses on the objects which Muslim migrants bring with them when they immigrate. This study occurs amidst challenges faced by members of the Muslim community following the Christchurch Mosque attacks on 15th March 2019. I approach the roles played by material objects by putting a lens on the past, present, and future biography of those thing. This focus upon the biography of objects supports a narrative inquiry into participants’ experiences, of six Muslim men and women living in Auckland, New Zealand. Using in-depth interviews with an open-ended interview schedule, my study explores the complex meaning those objects hold for the participants. Regarding ‘the past’ it finds that migrants chose objects with which to travel based on the utility of those objects, on the memories those objects hold, their status as gifts or as inheritance, and of the culture and faith they symbolise. Regarding ‘the present’, the findings indicate that the objects support the exercise of faith, the acquisition of knowledge and the holding to tradition within the migrants’ new environment. Regarding ‘the future’, the findings indicate that migrants want to pass their objects to their next generation for the maintenance of their identity, beliefs, memories and practices. This desire is shared by men and women. This thesis concludes that the objects with which Muslim migrants travel assist in the constant negotiation of the self, as occurs with the journey from migration to settlement.
Keywords: 441013 Sociology of migration, ethnicity and multiculturalism